DIALEKTIKA IMAN KRISTEN DAN KEBUDAYAAN INDONESIA DALAM KAJIAN GEERT HOFSTEDE - Edi Purwanto (Pengarah: Jurnal Teologi Kristen, 2019)
There are many facets of Christian faith, especially for Evangelicalism and Conservativism, which contradict with Indonesian culture according to Hofstede’s study. The aim of this study is synthesizing the dialectics utilizing Christ above Culrture concept of Niebuhr. This method of this study uses Hegel's dialectics to synthesize the dialectical relationship between Indonesian culture and Christian faith. The results of this study are syntheses of: (1) dialectics between individualistic doctrine of salvation and collectivistic of Indonesian culture; (2) dialectic of Christian faith and uncertainty avoidance culture; (3) dialectic of Christian faith on equality and power distance culture, (4 ) the dialectic of masculinity-femininity culture in the Christian faith and femininity of Indonesian culture; and (5) dialectic of long-term and short-term orientation in the Christian faith perspective and Indonesian culture. A number of alternative solutions are also proposed as practical applications of these syntheses for the gospel ministry in Indonesia that cannot avoid interaction with local cultures.